A comparative research on social styles and social contact and interaction behaviors in Celebes crested macaques (Macaca nigra) and Lion tailed macaques (Macaca silenus). - Muhammad Ashraf Mohd Salleh. (2010)
We studied 8 Lion Tailed and 7 Celebes Crested macaques, both representing the third and fourth grades respectively to seek whether 1) there will be a relation between social styles grading, and social contact and interaction behaviors and 2) there are significant differences in those behaviors between the Celebes Crested and Lion Tailed macaques since the fourth grade manifest higher tolerance level and higher tolerance level should reflect longer duration or more frequencies in social contact and interactions among individuals. Results showed that Celebes Crested as compared to Lion Tailed macaques engaged in significantly longer duration in grooming, huddling, proximity and aggression and not in mating, reconciliation, play biting, silent bare teeth and lips smacking. Limitations are discussed further.